Aplikasi Teknik Pizzicato Dalam Repertoar Spain Dan Donna Lee “Performance Of Bass” - Mhd. Zulfikri Wanas; Sastra Munafri; Zainal Warhat (Laga-Laga : Jurnal Seni Pertunjukan, 2023)
Pizzicato is a technique of playing a stringed instrument by plucking, which is playing the tone by plucking the strings using your fingers. This technique is generally played with the right hand, but can also be played with the left hand depending on the user. This technique is played in the presentation of Spanish and Donna Lee songs. Spain is an instrumental song by Jazz genre by Chik Corea. This work was made in 1971 in Spain. The title of this work is in accordance with the place of manufacture, namely Spain and in Indonesian is called Spanish. Donna Lee is a bebop Jazz instrumental song popularized by Charlie Parker. This composition was born in New York City, USA. In the beginning, this song was recorded by Charli Parker Quintet on May 8, 1947. Performance of Bass was the title of the performance. This show presents several repertoires, namely: Spain, Donna Lee, and several complementary repertoires of the show. The purpose of this show is to present a different musical performance to the audience with the aim of presenting something new through different repertoires. The methods used in this performance include the preparation stages, the training process, and the techniques used.Keywords: Pizzicato; Spain; Donna Lee; Performance of BassPizzicato adalah teknik memainkan alat musik dawai dengan cara di petik, yaitu memainkan nada dengan cara memetik senar dengan menggunakan jari.  Teknik ini umumnya dimainkan dengan tangan kanan, akan tetapi dapat juga dimainkan tangan kiri tergantung penggunanya. Teknik ini dimainkan dalam penyajian lagu Spain dan Donna Lee. Spain adalah lagu instrumental bergenre Jazz karya Chik Corea. Karya ini dibuat pada tahun 1971 di Spanyol. Judul dari karya ini sesuai dengan tempat pembuatannya yaitu Spain dan dalam bahasa Indonesia disebut Spanyol. Donna Lee adalah lagu instrumental bergenre bebop Jazz yang dipopulerkan oleh Charlie Parker. Komposi ini lahir di New York City, Amerika. Pada awlanya, lagu ini di rekam oleh Charli Parker Kuintet tanggal 8 Mei 1947. Performance of Bass adalah judul pertunjukan yang dilaksanakan. Pertunjukan ini menyajikan beberapa repertoar, yaitu: Spain, Donna Lee, dan beberapa repertoar pelengkap pertunjukan. Tujuan dari pertunjukan ini adalah menyajikan sebuah pertunjukan musik  yang berbeda kepada audiens dengan tujuan menampilkan sesuatu hal yang baru melalui repertoar yang berbeda-beda. Metoda yang dilakukan dalam pertunjukan ini diantaranya adalah tahapan persiapan, proses latihan, dan teknik yang digunakan.Kata Kunci: Pizzicato; Spain; Donna Lee; Performance of Bass